The Effect of Physiotherapy Manual Traction Techniques on the Western Ontario and McMaster University OA Index (WOMAC) in Knee Osteoarthritis Patients - Mutiara, Rizka; Ardinata, Dedi; Fachrina, Ririe; Vytra, Sunna; Lumongga, Firiani (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Age-related physical decline increases the risk of various diseases, including degenerative conditions, such as osteoarthritis (OA). OA is a chronic, progressive, multifactorial joint disorder characterized by cartilage deterioration, leading to chronic pain, stiffness, and impaired joint mobility. Knee OA significantly reduces patients' quality of life owing to functional limitations and pain. Manual traction therapy has shown potential in alleviating secondary inflammation in OA by lowering serum interleukin-1? levels and reducing pro-inflammatory cytokines and subchondral bone changes. This study aimed to assess the effect of manual traction physiotherapy on the Western Ontario and McMaster Universities Arthritis Index (WOMAC) in patients with knee OA. The study utilized a one-group pretest-post-test design, involving 36 participants selected through consecutive sampling from patients at the Sembiring Deli Tua Hospital Physiotherapy Clinic and Universitas Sumatera Utara's medical laboratory. Participants (aged 48–69 years, 80.6% female) underwent manual traction therapy twice a week for four weeks. The WOMAC questionnaire was used to evaluate changes in pain, stiffness, and physical function pre- and post-intervention. Statistical analysis using the Wilcoxon test revealed significant improvements across all WOMAC components, with pain scores decreasing from 14.81 to 7.58, stiffness scores from 4.0 to 2.5, and physical function scores from 30 to 23 (p < 0.001). These results demonstrate that manual traction therapy effectively reduces pain and stiffness while enhancing joint function in patients with knee OA.